GREEN SYNTHESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK DAUN PUCUK IDAT (Cratoxylum glaucum) SEBAGAI BIOREDUKTOR - Verry Andre Fabiani; Febry Sutanti; Desti Silvia; Megawati Ayu Putri (Indonesian Journal of Pure and Applied Chemistry, 2018)
An environment friendly technique for green synthesis of silver nanoparticles has been reported. Silver nanoparticle have been synthesized using water extract of leaves of pucuk idat (Cratoxylum glaucum), commonly known as local Bangka plant. The flavonoid and tannin present in the extract act as reducing agent. AgNO3 0,05 M solution was reducing using the extract at room temperature by stirring. Color changing of the solution was detected at 30 minutes reaction time. The color tends to be darker by the increasing of reaction time. Various techniques used to characterize synthesized nanoparticles are UV-Visible spectrophotometer, x-ray diffraction (XRD) and scanning electron microscopy (SEM). UV-Visible spectrophotometer showed absorbance peak in 405 nm, the XRD shows that silver nanoparticles formed are crystalline. The average particle size of Ag nanoparticles estimated from the Scherrer formula is 35,59 nm, while SEM image shows shape of silver nanoparticle is random and some spherical shape.